Genome size variation in Deschampsia cespitosa sensu lato (Poaceae) in Eurasia - Greimler, Josef; Temsch, Eva M.; Xue, Zhiqing; Weiss Schneeweiss, Hanna; Volkova, Polina; Peintinger, Markus; Wasowicz, Pawel; Shang, Hui; Schanzer, Ivan; Chiapella, Jorge Oscar (Plant Systematics and Evolution)
The grass Deschampsia cespitosa is a variable taxon out of which many varieties, subspecies and endemic species have been separated. In this paper, the variation in genome size (GS) and ploidy of this grass including several of its subspecies and two related species in Eurasia was investigated by flow cytometric (FCM) measurements. GS and ploidy data were also related to specific environments and reproduction mode. Ploidy levels found by FCM were confirmed by chromosome counts of diploid (2n = 28) and tetraploid (2n = 52) samples. Seminiferous (seed bearing) D. cespitosa was mainly diploid (GS between 3.754 and 5.438 pg/1C). GS variation in diploids showed a geographic pattern with a significant difference (H = 41,441, P < 0.001) between European (median = 4.377 pg) and Asian (median = 4.881 pg) accessions. Genome size (1C) in tetraploids ranged from 7.9426 to 9.0399 pg. Tetraploid seminiferous D. cespitosa was found mostly in disturbed habitats in western and southern Europe, while tetraploids in Asia were registered in wet Arctic habitats. Genome size (1C between 8.3278 and 8.8603 pg) of the pseudoviviparous plants (spikelets produce plantlets asexually) of wet habitats in central and northern Europe indicated tetraploidy. A putative triploid (GS 6.6817 pg) was detected in Iceland. Summing up, we found a high variation in GS on the geographic scale with significant regional differences in diploid D. cespitosa. Among the tetraploids, the asexually reproducing plants were bound to specific habitats, while the seminiferous plants showed a habitat preference similar to the diploids. Fil: Greimler, Josef. Universidad de Viena. Instituto de Botanica; Austria Fil: Temsch, Eva M. Universidad de Viena. Instituto de Botanica; Austria Fil: Xue, Zhiqing. Universidad de Viena. Instituto de Botanica; Austria Fil: Weiss Schneeweiss, Hanna. Universidad de Viena. Instituto de Botanica; Austria Fil: Volkova, Polina. Papanin Institute For Biology Of Inland Waters Ras; Rusia Fil: Peintinger, Markus. Swiss Federal ...